UAV-Based Intelligent Edge Computing - Choi , Won-Hyuck; Jo, Gyeong-Rae (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The growth of digital data has increased the importance of data processing and management. UAV-based communication networks leverage unmanned aerial vehicles to provide wireless services in remote areas. These systems have the potential to deliver high-speed data transfer, reliable connectivity, and improved network coverage, making them popular for various applications. The present study aimed to compare data processing time and latency between cloud computing (CC), edge computing (EC), and UAV-based intelligent edge computing (UEC). The performance differences of these three methods were analyzed as the number of nodes increased. The virtual environment was set up to give CC and EC penalties due to a lack of infrastructure resources, and under these conditions, UEC performed better than the other two methods. In addition, the study emphasizes on the importance and efficiency of UEC and presents the possibility and importance of building an advanced UAV communication network.